2016
DOI: 10.1088/1475-7516/2016/12/031
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational waves at interferometer scales and primordial black holes in axion inflation

Abstract: Abstract. We study the prospects of detection at terrestrial and space interferometers, as well as at pulsar timing array experiments, of a stochastic gravitational wave background which can be produced in models of axion inflation. This potential signal, and the development of these experiments, open a new window on inflation on scales much smaller than those currently probed with Cosmic Microwave Background and Large Scale Structure measurements. The sourced signal generated in axion inflation is an ideal ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
287
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(296 citation statements)
references
References 164 publications
6
287
0
Order By: Relevance
“…the Starobinsky-like class 28 with p = 2). As shown in [40], in the context of higher-dimensional couplings with Abelian 26 Higgs inflation corresponds to h(φ) = φ 2 . 27 However, it is crucial to stress that these expressions for n s − 1 and r only hold for large values of N .…”
Section: An Example: Attractor Modelsmentioning
confidence: 92%
See 1 more Smart Citation
“…the Starobinsky-like class 28 with p = 2). As shown in [40], in the context of higher-dimensional couplings with Abelian 26 Higgs inflation corresponds to h(φ) = φ 2 . 27 However, it is crucial to stress that these expressions for n s − 1 and r only hold for large values of N .…”
Section: An Example: Attractor Modelsmentioning
confidence: 92%
“…A viable model of PBH dark matter thus requires a non-trivial peaked structure of the primordial scalar power spectrum. It has been demonstrated that such spectra can be achieved in multifield models of inflation [14][15][16][17][18][19][20][21][22][23] or by arranging for the corresponding features in the scalar potential of inflation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, laser interferometer gravitational wave observatories are sensitive to the GWB today, and provide probes of much smaller scales: k CMB ∼ 10 −4 Mpc −1 vs. k interf ∼ 10 13 Mpc −1 [20]. In the case of single-field slow-roll inflation the tensor spectrum is expected to have a small red-tilt (n T = −r/8, where n T is the tilt of the tensor spectrum P h ∼ k n T ), in which case modern interferometers would not be sensitive enough to make a detection.…”
Section: Introductionmentioning
confidence: 99%
“…Other models of PBH production not considered here can be found in Refs. [27,[46][47][48][49][50]. For each model, we calculate the resulting SGW spectrum.…”
Section: Models Of Primordial Scalar Spectramentioning
confidence: 99%